The sinking of Titanic - Bodden, Valerie (Bodden, Valerie. Disasters for all time., 2019)
Highlights the events leading up to and following the sinking of the "Titanic." Also discusses its discovery and salvage. Includes primary source quotes, a glossary, a timeline, resources for further information, and photographs.